Sampling effort analysis for hymenopteran parasitoids in three environments of Eastern Uruguay (INNOTEC, 2017)
Hymenopteran parasitoids offer an ecosystem service as biological control of agricultural pests. Many of these parasitoids are tiny insects and, therefore, their screening and identification are highly complex. Fortnightly sampling, between December 2014 and December 2015, was conducted with two Malaise traps in three areas: natural area, cattle grazing pastures and cattle grazing with winter-summer agriculture, near Castillos, Rocha, Uruguay. Taxa were screened at the Centro Universitario Regional del Este (CURE) – Rocha and parasitoids identification, at family level of the order Hymenoptera, was made in Ribeirão Preto, Brasil. In total, 36.718 parasitoid individuals from 31 Hymenoptera families were collected. Data sets were created with information transformed to proportional abundance in the sample: considering one (N = 72) or two (N = 144) fortnights, and a family accumulation multivariate analysis was applied (perMANOVA). Considering half (one fortnight) or total (two fortnights) number of sampling dates, indistinctly, it is possible to adjust sampling effort in order to decrease the sampling frequency or dates, without a significant reduction on the recovering of new families. Thus, this is a contribution to maintain the recovery efficiency and the value of the study, while helping to reduce costs in material and human resources.
Keywords: Hymenoptera parasitica; Malaise traps; abundance; diversity